Correlation between aflatoxin M1 content of breast milk, dietary exposure to aflatoxin B1 and socioeconomic status of lactating mothers in Ogun State, Nigeria - Adejumo, O.; Atanda, O.; Raiola, A.; Somorin, Y.; Bandyopadhyay, Ranajit; Ritieni, A. (Elsevier, 2013)
Aflatoxin M1 (AF M1), a hydroxylated metabolite of AF B1, is an important toxin that can contaminate themilk of lactating mothers. A correlation study was conducted to determine the relationship between AFM1 content of breast milk, dietary exposure to AF B1 and socioeconomic status of lactating mothers in thethree Senatorial districts of Ogun State, Nigeria. Equal amounts of breast milk (20 ml) and food rations(40 kg) obtained from 50 volunteer lactating mothers and eighty-two frequently consumed food commoditiesin the preceding month were used for the study. The level of contamination of the foods byAF B1 was low (0.16–0.33 lg/kg) and differed significantly (p < 0.05) across the state but did not exceedthe EU limit of 2 lg/kg. The occurrence level of AF B1 was however high (93.75–94.45%) and was morepronounced in Ogun East Senatorial district (94.45%). Eighty-two percent of the breast milk was contaminatedwith AF M1 (3.49–35 ng/l) and 16% exceeded the EU limit of 25 ng/l while a 100% occurrence riskwas recorded in Ogun Central Senatorial district. The socioeconomic status of the mothers also significantlyinfluenced their dietary exposure and exposure risk of the sucklings to AF M1